Ответы и объяснения

  • Voxman
  • главный мозг
2013-06-02T00:13:54+04:00

 

2cos^2x = \sqrt{3}sin(\frac{3\pi}{2} + x)\\\\ sin(\frac{3\pi}{2} + x) = -cosx\\\\ 2cos^2x = -\sqrt{3}cosx\\\\ 2cos^2x + \sqrt{3}cosx = 0\\\\ cosx(2cosx + \sqrt{3}) = 0\\\\ 1) \ cosx = 0\\\\ x = \frac{\pi}{2} + \pi n, \ n \in Z\\\\ 2) \ 2cosx + \sqrt{3} = 0\\\\ cosx = -\frac{\sqrt{3}}{2}\\\\ x = \pi - \frac{\pi}{6} + 2\pi n, \ n \in Z\\\\ x = -\pi + \frac{\pi}{6} + 2\pi n, \ n \in Z

 

В искомый отрезок попадают следующие корни (это отчетливо видно из Рис. 1):

 

 

x = \frac{3\pi}{2},\\\\ x = \frac{5\pi}{2},\\\\ x = 3 \pi - \frac{\pi}{6} = \frac{17\pi}{6}